Exploring Effects of Chitosan Oligosaccharides on Mice Gut Microbiota in in vitro Fermentation and Animal Model - Zhang, Chen; Jiao, Siming; Wang, Zhuo A.; Du, Yuguang (Frontiers in Microbiology, 2018)
Chitosan oligosaccharides (COS) have shown positive effects on host gut health and influence on intestinal microbial community. However, the bioactivity and mechanism of COS on gut microbiota is still poorly understood. Here, we presented systematic studies of COS on mice fecal/gut microbiota. During in vitro fermentation of COS by mice gut microbiota, total bacterial population significantly decreased after 8-hour COS treatment but was returned to the normal level after extended incubation. Consumption of COS and production of SCFAs suggested that COS were utilized by the microbe, although the consumption of chitosan pentasaccharides was obviously slower than others. COS treatments on mice fecal samples caused the decrease of potential pathogenic genera Escherichia/Shigella and the increase of genus Parabacteroides. In vivo animal study indicated that COS reduced population of probiotic genera Lactobacillus, Bifidobacterium and harmful genus Desulfovibrio, and increased abundance of genus Akkermansia. Phylum Proteobacteria was significantly inhibited by COS both in the animal model and in vitro fermentation. Our findings suggested that COS could reform the community structure of gut microbiota. The relationship among COS, gut microbiota and host health deserve further study.